How Person-Organization Fit Impacts Employees' Perceptions of Justice and Well-Being - Roczniewska, Marta; Retowski, Sylwiusz; Higgins, E. Tory (Frontiers in Psychology, 2018)
Regulatory fit theory predicts that when individuals adopt strategies that sustain their motivational orientations, they feel right about what is happening. Our aim was to test these predictions at the person-organization level. Across three studies, we expected and found that feeling right experience that results from a match between an employee and an organizational climate produces perceptions that the company’s prevailing procedures are fair. In Study 1 (N=300), a survey among employees of distinct companies, we observed that the more organizational characteristics matched individual promotion and prevention focus of the employees, the more the employees perceived their workplace as just. Study 2 (N=139), a randomized-control experiment, replicated this pattern by demonstrating that individuals with a predominant promotion focus assigned fairness to the organizational conduct most strongly when they recalled events characterizing a promotion-oriented environment; on the contrary, individuals with a predominant prevention focus deemed their workplace most fair when they were asked to recall prevention-related conduct of their company. In Study 3 (N=376), a cross-sectional field study, we found that regulatory non-fit was associated with lower procedural justice perceptions and this, in turn, related to higher burnout. Theoretical and practical implications of applying regulatory fit theory to person-organization relationships are discussed.